The Centrality and Interpretation of Psalms in Judaism prior to and during Medieval Times: Approaches, Authorship, Genre, and Polemics - Kalimi, Isaac (The review of rabbinic Judaism, 2020)
This study discusses the centrality of the book of Psalms among the Jews and in Judaism. It outlines the seven most important and influential rabbinic exegetical works on Psalms, in the period before and during the medieval age: Targum Psalms and Midrash Psalms Shocher Tov, from some time in the Talmudic period; and five prominent medieval commentaries: Saadia Gaon, Moses haCohen ibn Gikatilla, Rashi, Abraham ibn Ezra, and David Kimchi. I briefly introduce each interpretative work and focus on selected aspects: The commentators’ distinct exegetical methods, their approaches to the questions of the authorship and genre of Psalms, and polemics with inside (e.g., Karaites) and outside (e.g., Christians) opponents. The result is to analysis and synthesis their approaches and to show the various trends that rabbinic Psalms interpretation took in these periods.